Comparative Evaluation of Diagnostic Challenges and Long-Term Outcomes in Early-Onset Schizophrenia - Nasir Ali, Benazir Javed, Syed Muhammad Omer, Syed Naveed Haider, Maha Abdullatif, Zeinab Alaagib Ahmed Kara, Saleha Saboor (Pakistan Journal of Medical & Health Sciences, 2024)
Background: Early-onset schizophrenia (EOS), defined by psychotic symptom onset before 18 years of age, is associated with a more severe clinical trajectory and presents unique diagnostic and therapeutic challenges. Compared to adult-onset schizophrenia (AOS), EOS patients often experience delayed diagnosis, higher relapse rates, and poorer functional outcomes, especially in low-resource settings like Pakistan where early psychiatric symptoms are frequently underrecognized. Aims and Objectives: This study aimed to compare the diagnostic challenges and long-term clinical and functional outcomes between EOS and AOS, and to identify predictors of poor prognosis in EOS patients to inform early intervention strategies. Methodology: This was a retrospective comparative clinical study conducted at Sir Ganga Ram and Services Hospital, Lahore, from June 2022 to May 2023. A total of n=70 patients diagnosed with schizophrenia per DSM-5 criteria were divided equally into EOS (n=35) and AOS (n=35) groups. Data were collected on sociodemographic, symptom severity (PANSS), functional status (GAF), treatment delays, relapse rates, and hospitalizations. Logistic regression was performed to determine predictors of poor functional outcomes in EOS. Results: EOS patients had significantly longer duration of untreated psychosis (p=0.002), higher PANSS scores (p=0.01), more relapses and hospitalizations (p<0.001), and lower GAF scores (p<0.001) compared to AOS. Predictors of poor outcomes included prolonged DUP (OR=1.25), lower education (OR=0.88), and lower socioeconomic status (OR=0.95). Conclusion: EOS is associated with worse clinical and functional outcomes than AOS, driven by diagnostic delays and sociodemographic disadvantages. Early detection and targeted interventions are crucial to improve long-term prognosis in this vulnerable population. Keywords: Early-Onset Schizophrenia, Adult-Onset Schizophrenia, Diagnostic Challenges, Duration of Untreated Psychosis, Prognosis, Functional Outcomes.